2022
DOI: 10.1186/s40854-021-00319-0
|View full text |Cite
|
Sign up to set email alerts
|

Cue the volatility spillover in the cryptocurrency markets during the COVID-19 pandemic: evidence from DCC-GARCH and wavelet analysis

Abstract: This study investigates the dynamic mechanism of financial markets on volatility spillovers across eight major cryptocurrency returns, namely Bitcoin, Ethereum, Stellar, Ripple, Tether, Cardano, Litecoin, and Eos from November 17, 2019, to January 25, 2021. The study captures the financial behavior of investors during the COVID-19 pandemic as a result of national lockdowns and slowdown of production. Three different methods, namely, EGARCH, DCC-GARCH, and wavelet, are used to understand whether cryptocurrency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 91 publications
(87 reference statements)
1
16
0
Order By: Relevance
“…Notably, BTC has greater wavelet coherence with ETH than any other cryptocurrency. This finding is consistent with the findings of Yousaf and Ali (2020), Ji et al (2019), andÖzdemir (2022). This indicates that the comovement effects between BTC and ETH are relatively stronger between mid-2020 and early 2022 in the 4-to-128-day frequency band.…”
Section: Time-frequency Comovement Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, BTC has greater wavelet coherence with ETH than any other cryptocurrency. This finding is consistent with the findings of Yousaf and Ali (2020), Ji et al (2019), andÖzdemir (2022). This indicates that the comovement effects between BTC and ETH are relatively stronger between mid-2020 and early 2022 in the 4-to-128-day frequency band.…”
Section: Time-frequency Comovement Analysissupporting
confidence: 92%
“…In this context, several studies have also confirmed that the COVID-19 pandemic has exerted significant impacts on the interactions among cryptocurrencies (e.g. Yousaf and Ali 2020;Polat and Günay 2021;Naeem et al 2021;Demiralay and Golitsis 2021;Raza et al 2022;Kumar et al 2022;Özdemir 2022;Ahmed and Sleem 2022). More importantly, asymmetric characteristics, tail risk, extreme volatility, and pricing bubbles in the cryptocurrency market have all been identified during the COVID-19 pandemic (see Nguyen et al 2020;Xu et al 2021;González et al 2021;Apergis 2022;Iqbal et al 2021;Montasser et al 2022;Ahn 2022;Shahzad et al 2022).…”
Section: Introductionmentioning
confidence: 82%
“…pre-pandemic and pandemic periods. This analytical tool captures low and high scale impacts of shocks between sectors by decomposing the time series into various frequency components across time making the tool technically superior in connectedness analyses (Özdemir, 2022). WCA is built up by two main components, namely the cross-wave transform (CWT) and coherence (Torrence and Compo, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al ( 2021 ) attempted to determine the role of downside risk in determining returns in the crypto money market through portfolio analysis and Fama–MacBeth regressions and could not find a relationship between them. Özdemir ( 2022 ) analyzed the daily closing prices of eight cryptocurrencies (BTC, ETH, Stellar, XRP, Tether, ADA, LTC, and EOS) using the E-GARCH and DCC-GARCH model and determined that volatility changed because of increasing uncertainty and risk during the coronavirus (COVID-19) pandemic.…”
Section: Literaturementioning
confidence: 99%